The Relationship between Family's Assessment Support and MDR TB Patient's Adherence on Treatment in RSUD Dr. Soetomo Surabaya - Ainiyah, Safira Nur; Soedarsono, Soedarsono; Umiastuti, Pirlina (Universitas Airlangga, 2019)
Introduction: Multi Drug-Resistant Tuberculosis (MDR TB) is caused by Mycobacterium tuberculosis and has been resistant to isoniazid and rifampicin. Its treatment needs long time and causes some side effects which can make the patients non-adherent so that family support is needed. This study aims to know the relationship between family's assessment support and MDR TB patient's adherence on treatment in RSUD Dr. Soetomo Surabaya. Methods: This was an analytic observational cross-sectional study, to know the frequency distribution of family's assessment support, MDR TB patient's adherence, and the relationship between them in 24 MDR TB patients, recruited from MDR TB Clinic, RSUD Dr. Soetomo, Surabaya, from October 2017 to June 2018 and their family. The analysis was descriptive statistic and inferential statistic using Fisher Exact Test. Results: The results of this study showed that 83.3% of MDR TB patients' family give high assessment support and 58.3% of MDR TB patients in RSUD Dr. Soetomo from October 2017 to June 2018 have high adherence on treatment. There is significant (p = 0.020), moderate (c = 0.468), and direct relationship between family's assessment support and MDR TB patient's adherence on treatment in RSUD Dr. Soetomo Surabaya. Conclusion: To improve MDR TB patient's adherence on treatment, family must give high assessment support.